Evaluation of Tear Secretion and Tear Film Stability in Patients with Pterygium and Normal Individuals (Med Phoenix, 2022)
Introduction: Abnormalities of any of the components of lacrimal function unit can lead to dysfunctional tear film and development of dry eye. Dry eye is a commonly encountered problem in general population.Materials and Methods: A hospital-based, case-control study was conducted at National Medical College and Teaching Hospital, Nepal from 1st August 2018 to 30th July 2019.  A total of 279 participants: 93 cases of pterygium (Group A: case) and186 (Group B: control) normal individuals with no ocular surface disorder were enrolled. Objective analysis was done by Schirmer’s (SCH) without and with anesthesia and Tear Break up Time (TBUT). Dependent t test was used to analyze the data. P value